Robot‐assisted thymectomy in large anterior mediastinal tumors: A comparative study with video‐assisted thymectomy and open surgery. Issue 3 (25th November 2022) - Jiang, Bin; Tan, Qun‐You; Deng, Bo; Mei, Long‐Yong; Lin, Yi‐Dan; Zhu, Long‐Fei
Abstract: Background: The aim of this study was to evaluate the safety and effectiveness of robot‐assisted thymectomy (RAT) in large anterior mediastinal tumors (AMTs) (size ≥6 cm) compared with video‐assisted thymectomy (VAT) and open surgery. Methods: A total of 132 patients with large AMTs who underwent surgical resection from January 2016 to June 2022 were included in this study. A total of 61 patients underwent RAT, 36 patients underwent VAT and 35 patients underwent open surgery. Perioperative outcomes were compared. Results: There were no significant differences in tumor size ( p = 0.141), or pathological types ( p = 0.903). Compared with the open group, the RAT and VAT groups were associated with a shorter operation time (115.00 vs. 160.00, p = 0.012; 122.50 vs. 160.00, p = 0.071), and less blood loss (50.00 vs. 200.00, p < 0.001; 50.00 vs. 200.00, p < 0.001), respectively. The rate of conversion in the RAT group was similar to that in the VAT group (6.56% vs. 13.89%, p = 0.229). Concomitant resection was less frequently performed in the VAT group than in the RAT and open groups (5.56% vs. 31.15%, p = 0.040; 5.56% vs. 31.43%, p = 0.006). VAT patients had a lower drainage volume (365.00 vs. 700.00 and 910.00 mL, p < 0.001), shorter duration of chest tube (2.00 vs. 3.00 and 4.00, p < 0.001), and shorter hospital stay (5.00 vs. 6.00 and 7.00, p < 0.001) than the RAT and open groups. There was no 30‐day mortality in any group. No difference was seen in R0 resection rates ( p = 0.846). The postoperative complication rates were similar among the three groups ( p = 0.309). Total in‐hospital costs (66493.90 vs. 33581.05 and 42876.40, p < 0.001) were significantly higher in the RAT group. Conclusions: RAT is safe and effective for the resection of large AMTs compared to VAT and open surgery. Vascular resection in RAT is technically feasible. A long‐term follow‐up is required. Abstract : The robot‐assisted thymectomy (RAT) can be performed using various approaches. The sub‐xiphoid approach is routinely selected for centered and advanced large AMTs in our center; it can provide excellent visualization for exposing the proximal and distal ends of the innominate vein, which is convenient for resection of the invaded innominate vein, even for partial resection of the superior vena cava (SVC).